Cell pattern abnormalities in cervical pap smear in correlation with age and demography at a Tertiary care centre. - Dr. N. Thamarai Selvi; Dr. Revathi Shree R; Dr. Prakashiny S. (Tropical Journal of Pathology and Microbiology, 2021)
Introduction: Carcinoma Cervix is common all around the globe and ranked third amidst all malignancies among women. The cervical mucosa undergoes morphologic variation with age and practising cytopathologists is aware of these difference to make an accurate diagnosis. This study aimed to detect abnormal cervical epithelial cell patterns in a rural population and compare lesions or abnormal cell patterns among different age groups. Materials and Methods: This is a cross-sectional, descriptive study conducted in a tertiary care centre at the Department of Pathology over 6 months. 408 women were included in the study. Data were entered in Microsoft Excel and analyzed in SPSS software. Results: Out of 408 women included in the study, the most common age group of the presentation was 31 to 40 years (36%), followed by 20 to 30 years (24%). NILM-Inflammatory was the most common finding (50%), followed by NILM (36%). The most common symptoms of presentation were Menstrual abnormalities (21%), White discharge and pruritus (18%). Findings in younger women were most commonly NILM-Inflammatory & NILM whereas in the post-menopausal age group, ASCUS, LSIL & HSIL. Conclusion: All women above 30 years of age should undergo routine cervical cancer screening, and should continue screening even in the perimenopausal and postmenopausal age. Most women who visited the gynaecology OPD were not aware of cervical cancer screening. Hence the general population has to be educated about the benefits of pap smear test through medical camps and awareness programs.